Soft-starting scheme for a DC solid-state transformer based on a modular multilevel converter - Zhendong Ji (Elsevier, 2021)
Direct current (DC) solid-state transformers based on modular multilevel converters (MMC-DCSSTs) have wide application prospects in DC transmission and distribution systems. However, after starting such a system, the normal operation of its MMC-DCSST​ may generate relatively large inrush and magnetizing currents on the primary and secondary sides. In this study, a soft-starting scheme for MMC-DCSSTs, which is divided into the primary-side and secondary-side charging stages, has been designed to limit these currents before the system reaches the normal operation stage. The effectiveness of the proposed method is validated experimentally, and the reliability of MMC-DCSSTs can be improved with the controllable currents.